Recent Progress in the Synthetic Methods of Pyrazoloquinoline Derivatives - Borik, Rita M.; Mostafa, Mohamed S.; Behalo, Mohamed S.; Khidre, Rizk E. (Current Organic Chemistry, 2024)
The focus of this review is on the synthetic routes available for different types of pyrazoloquinoline derivatives. There are three types of synthetic methods: i) from pyrazole derivatives; ii) from quinoline derivatives; and iii) miscellaneous methods. The position of the linkage between pyrazole and quinoline rings determines the seven isomers of pyrazoloquinolines. The purpose of this review is to provide a guide for both synthetic and medicinal chemists to discover and design new pyrazoloquinolines for medical purposes.
Keywords: pyrazoloquinoline